2003
DOI: 10.1046/j.1537-2995.2003.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy in blood and marrow transplant patients receiving tacrolimus or cyclosporine A

Abstract: In this study, a high incidence of TMA was found in patients receiving either CSA or FK-506 following BMT, with uniform diagnostic criteria and strict monitoring. Neither drug showed elevated levels in most patients with TMA. Plasmapheresis was unsuccessful in reversing most cases of TMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 31 publications
2
44
1
1
Order By: Relevance
“…Calcineurin inhibitors are known to cause microangiopathy and several studies 17,31,37 have attributed TAM to CsA toxicity, whereas others have described TAM in patients off CsA. 11 We could not analyze CsA use vs none, as all patients analyzed had CsA (with the exception of twins).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcineurin inhibitors are known to cause microangiopathy and several studies 17,31,37 have attributed TAM to CsA toxicity, whereas others have described TAM in patients off CsA. 11 We could not analyze CsA use vs none, as all patients analyzed had CsA (with the exception of twins).…”
Section: Discussionmentioning
confidence: 99%
“…This is of importance as CsA is withdrawn in patients with TAM in many centers; others switch treatment to alternative drugs. [37][38][39] The higher incidence of C. difficile positive diarrhea in patients with TAM vs no TAM is of interest, but remains unexplained. Pseudomembraneous colitis may be associated with RBC fragmentation and the hemolytic uremic syndrome in patients with C. difficile colitis has been described.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This uncertainty in diagnosis has led to wide variations in the reported incidence of TA-TMA, a lack of consensus regarding clinical approach to management, and poor understanding of prognostic factors with respect to therapeutic response and survival. [1][2][3][4][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] To address this issue of diagnostic clinical uncertainty, two new diagnostic criteria for TA-TMA have recently been proposed; the Bone Marrow Transplant Clinical Trials Network (BMT-CTN) and the IWG (International Working Group) TA-TMA criteria. 24,25 However, neither criterion has been rigorously evaluated clinically, and issues remain with respect to the diagnostic sensitivity of both.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent publications have suggested that PE has limited efficacy in treatment of TA-TMA, with relatively low response rates (20-50%) in comparison to idiopathic TTP (75%) generally reported. 2,3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] This overall poor response to PE in TA-TMA is not necessarily surprising in light of recent insights into its pathogenesis, which suggest that TA-TMA is, in fact, a multifactorial disorder resulting from endothelial cell dysfunction secondary to a variety of insults, including immunosuppressive medications, GVHD and (especially viral) infection. 2,3,8 Unlike idiopathic TTP, TA-TMA has only rarely been associated with severe deficiency of the plasma protease ADAMTS13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation